Hipertensão arterial e fatores associados em usuários do Programa de Saúde da Família de São Francisco do Conde, Bahia, Brasil - Damas, Liliane Vidal de Oliveira (2016)
the Systemic Arterial Hypertension is a severe public health condition of high prevalence and is also the main risk factor for cardiovascular as well as brain vascular conditions in the industrialized countries and in the developing nations such as Brazil. Objective: to estimate the prevalence of Systemic Arterial Hypertension and factors linked to adult individuals, and users of Family Health Program in São Francisco do Conde city, State of Bahia. Methodology: Population based and transversal cut study with a sample of 456 individuals of ages equal or superior to eighteen (and enrolled in the program) which was performed in São Francisco do Conde city, State of Bahia. The used the prevalence ratio as a measure of association and the confidence interval (CI - 95%) as a measure of statistical significance to measure the association between sociodemographic, anthropometric, lifestyle and hypertension. For the he multivariate analysis the Poisson regression model was employed. Outputs: The prevalence of hypertension was of 51.80%, among men was 53.90% in individuals with overweight was 57.95% among individuals aged ≥ 40 years was 72.08% among those with abdominal adiposity was 58.51%. HA showed a statistically significant association in crude and adjusted analysis with age ≥ 40 years, low consumption of fat and abdominal fat. Conclusion: there was a high prevalence of hypertension especially among individuals aged ≥ 40 years and among those who presented abdominal adiposity. The integrated work of the multidisciplinary team in the Family Health Program can contribute to the prevention and control of this disease, identification of suspects, motivation for adherence to guidelines higienodietéticas and antihypertensive drug treatment.